The Importance of Intra-Organizational Networking for Younger Versus Older Workers: Examining a Multi-Group Mediation Model of Individual Task Performance Enhancement - Van der Heijden, Beatrice I. J. M.; Kruyen, Peter M.; Notelaers, Guy (Frontiers in Psychology, 2020)
The purpose of this paper is to investigate the effect of intra-organizational networking on individual task performance, via employability. Moreover, this study also examines whether this relationship differs for younger (< 40 years) versus older employees (≥ 40 years). A self-report questionnaire was distributed among a sample of employees working in a range of different types of organizations (n = 374). We conclude that employability fully mediates the relationship between intra-organizational networking and individual task performance. However, this mediation effect did not vary between younger and older employees. This study extends past research by applying a human capital perspective (in particular, social capital) and life-span development frameworks for explaining employability and task performance enhancement across one’s working life. It provides useful insights for stimulating career development and individual performance growth, by means of social capital, herewith increasing the individual employee’s chance to survive in nowadays’ labor markets.